Economics and Its Discontents: Comments on George DeMartino's The Economist's Oath. Issue 1 (2nd January 2016) - Freeman, Alan
Abstract : George DeMartino's The Economist's Oath is provoking timely and welcome discussions in economics. This essay assesses the close connection between the ethical dimension of economics and the concept of pluralism, which has become a focus of dissent within economics, especially in the UK and Europe. Both concerns, it argues, arise from the current "theoretical crisis of economics"—a term coined by Joan Robinson in the 1970s and updated in this essay to reflect the present state of the discipline of economics. It argues that pluralism in fact is an ethical as well as scientific response to this theoretical crisis, and it develops the case for ethical guidelines that codify the pluralist responsibilities of an economist.